Phytochemical Screening, HPTLC Finger Print and in vitro Antioxidant Activity of Bark Extracts of Lannea coromandelica (Houtt.) Merr. - R, Rajesh. (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Lannea coromandelica Merr (Houtt.) is used as a common medicinal plant among the tribal communities of Bangladesh has long been used in indigenous medicine for curing certain health disorders. Phytochemicals present in the bark are associated with their therapeutic capabilities. Objectives: The study was aimed to evaluate the HPTLC finger printing and in vitro antioxidant activity of methanol extract (MELC) and aqueous extract (AELC) of L. coromandelica bark extracts. Materials and Methods: The study consists of parameters which includes moisture content, ash values and ethanol and water soluble extractive values. Results: HPTLC finger print assessment will help to identify and monitor the drug effectiveness and ensure therapeutic efficacy. Antioxidant activity was measured using in vitro methods such as total phenolic content, total flavanoid content, 1,1 diphenyl 2 picryl hydrazyl (DPPH) radical scavenging potential, ferric ion reduction assay and phosphomolybdenum assay at different concentrations. MELC showed a high phenolic, flavanoid content, higher DPPH free radical scavenging, lower antioxidant ability of ferric ions and a phosphorous molybdenum assay compared to that of standard. Conclusion: The presence of natural phytoconstituents which are responsible for antioxidant activity in plant extracts. This may aid in further extensive studies for identifying and isolating compounds with potential therapeutic value in Lannea coromandelica (Houtt.) Merr.
Keywords: Lannea coromandelica houtt; Phytochemistry; in vitro antioxidant activity; Physicochemical parameters; HPTLC